DETERMINASI PERTUMBUHAN EKONOMI DIGITAL DI INDONESIA: BUKTI DARI DATA PANEL 34 PROVINSI, 2019–2024 - Chan, Nuraini; Entaresmen, R. Ajeng; Shalahudin, Ziad Aljundi; Susanti, Azizah Amelia Eka (Media Ekonomi, 2026)
This study examines how MSMEs, government investment, and digital literacy relate to digital economic growth across Indonesia, using panel data from 34 provinces between 2019 and 2024. Data were drawn from BPS and relevant government agencies. The study applies panel data regression to capture variation across both time and geography. Three model specifications were tested: Fixed Effects, Common Effects, and Random Effects. To select the best fit, two tests were performed — the Chow Test, which compared Common Effects against Fixed Effects, and the Lagrange Multiplier (LM) Test, which compared Common Effects against Random Effects. Findings from both tests identified the most appropriate specification for the data. MSMEs and government investment both show positive, statistically significant effects on digital economic growth. Digital literacy, however, does not. This suggests that simply expanding infrastructure or growing the number of MSMEs is not enough — the quality of human resources matters too, and current policy may be underweighting it.